Commentary: The New Pedagogy: Students and Teachers as Learning Partners (LEARNing Landscapes, 2013)
There is currently a powerful push-pull factor in schooling. The push factor is that school is increasingly boring for students and alienating for teachers. The pull factor is that the exploding and alluring digital world is irresistible, but not necessarily productive in its raw form. The push-pull dynamic makes it inevitable that disruptive changes will occur. I have been part of a group that has been developing innovative responses to the current challenges. This response consists of integrating three components: deep learning goals, new pedagogies, and technology. The result will be more radical change in the next five years than has occurred in the past 50 years.
Keywords: push-pull factor; schooling; deep learning goal; new pedagogies; technology; change